Experience of Hydatid Cyst Management in a Tertiary Care Center in Kathmandu Nepal - Joshi, Bijendra D; Koirala, Udaya; Joshi, Arbin; Dhital, Saroj P; Dhoubadhel, Prativa (Journal of Institute of Medicine Nepal, 2020)
Introduction Hydatid cyst is a common disease in Asian subcontinent produced by the larval stage of Echinococcus granulosus. The most common site of involvement is the liver. The mode of presentation can vary. The management of hydatid cyst includes medical treatment with albendazole, ultrasound guided aspiration and instillation of scolicidal agents as well as surgical treatment. Surgery can be perfomed by open or laparoscopic approach. The aim of this study is to analyze the cases of hydatid cyst of liver managed in our set up. Methods This is a retrospective study of 45 patients with hydatid cyst managed in Kathmandu Model Hospital over the last five years. Data were collected from the patients hospital records. Demographic parameters, chief complains, radiological findings, anti echinococcal immunglobulin findings, mode of management,complications of surgery were evaluated. Results Majority of our patients were female (66.7%). Mean age of the patients were 39±17.2 years (16 to 89 years).Most common symptom of presentation was pain in right upper quadrant of abdomen.Most common site of involvement was liver (93.33%)followed by spleen (4.4%). There was one case of ruptured pulmonary hydatid cyst which was referred.Operative management was done in patients (17.77%) out of which five patients (62.5%) underwent laparoscopic partial pericystectomy and omentoplasty.No major complications were encountered in any of the cases managed surgically. Conclusion Majority of cases occured in liver. Most cases were managed conservatively. Laparoscopic management of hydatid cyst is effective.